(3GdbUjOI GdgeRjI aj GdeOGFM GdfHhjIs - (3GdUfgGLj GdHhUjQj GdeUQj, CHh YHO Gddg, TQa GdOjf , eMeO Hf SYjO Hf MeGO Hf YHO Gddg, (B696 (3g`s ((3EHQGgje Hf ESeGYjd GdYOhjs)
(3ChdgG (B:s
(3bGd GdYdGeI GHf MLQ Gdecj eJQLeG dSjOj eDda GdgeRjI hfGXegGs
(3BNQgG (B:s
(3eG CbGe GdUdGI ef YHO Gddg (B- (3hbGeJ HQHgG GdCTjGA JeJ GdMeO ddg hMSf Jhajbgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 139s
(3eYLe GdeDdajf(B: 3 / 317s
(3cTa GdXfhf(B: 2 / 1349s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs